Caste : the origins of our discontents - Wilkerson, Isabel, ....- ([London] : Penguin Books, 2023)
Beyond race or class, our lives are defined by a powerful, unspoken system of divisions. In Caste, Pulitzer Prize-winning author Isabel Wilkerson gives an astounding portrait of this hidden phenomenon. Linking America, India and Nazi Germany, Wilkerson reveals how our world has been shaped by caste - and how its rigid, arbitrary hierarchies still divide us today. With clear-sighted rigour, Wilkerson unearths the eight pillars that connect caste systems across civilizations, and demonstrates how our own era.
Keywords: Sociale ongelijkheid -- Verenigde Staten